Dyskeratosis congenita: a case report on a rare disease - Khaliq, Sehar; Syed Kumail Hasan Kazmi (Journal of the Pakistan Medical Association, 2020)
Abstract Dyskeratosis congenita is a very rare inherited haematological disorder characterised by a classical clinical triad of leukoplakia, skin pigmentation and dystrophied nails. Here is a case of a young patient who presented with brittle nails, lacy hyperpigmentation of the skin and leukoplakia along with pancytopenia. Haematopoietic stem cell transplantation is the only cure for this disease but due to financial constraints of the family it was not possible. The patient was placed on androgen therapy and showed favourable response but later was lost to follow-up. Keywords: Dyskeratosis Congenita, Pancytopenia, Continuous...